Intelligent interactive multimedia systems and services - Tsihrintzis, George A. (Springer Berlin Heidelberg, 2010)
This volume contains the Proceedings of the 3nd International Symposium on Intelligent Interactive Multimedia Systems and Services (KES-IIMSS 2010). This third edition of the KES-IIMSS Symposium was jointly organized by the Department of Informatics of the University of Piraeus, Greece and the Department of Information Technologies of the University of Milan, Italy in conjunction KES International. Adapting Spreading Activation Techniques towards a New Approach to Content-Based Recommender Systems -- A Framework for Automatic Detection of Abandoned Luggage in Airport Terminal -- Modeling Student’s Knowledge on Programming Using Fuzzy Techniques -- Camera Angle Invariant Shape Recognition in Surveillance Systems -- Multicriteria-Based Decision for Services Discovery and Selection -- Building a Minimalistic Multimedia User Interface for Quadriplegic Patients -- Biofeedback-Based Brain Hemispheric Synchronizing Employing Man-Machine Interface -- Performance of Watermarking-Based DTD Algorithm under Time-Varying Echo Path Conditions -- Applying HTM-Based System to Recognize Object in Visual Attention -- Constant Bitrate Image Scrambling Method Using CAVLC in H.264 -- Color Image Restoration Technique Using Gradient Edge Direction Detection -- Watermarking with the UPC and DWT -- Building a Novel Web Service Framework -Through a Case Study of Bioinformatics -- An Architecture for Collaborative Translational Research Utilizing the Honest Broker System -- Simulated Annealing in Finding Optimum Groups of Learners of UML -- A Smart Network Architecture for e-Health Applications -- A Music Recommender Based on Artificial Immune Systems -- The iCabiNET System: Building Standard Medication Records from the Networked Home -- Multi-agent Framework Based on Web Service in Medical Data Quality Improvement for e-Healthcare Information Systems -- Towards a Unified Data Management and Decision Support System for Health Care -- A Glove-Based Interface for 3D Medical Image Visualization -- Open Issues in IDS Design for Wireless Biomedical Sensor Networks -- Context-Aware Notifications: A Healthcare System for a Nursing Home -- Multimodality in Pervasive Environment -- Optimizing the Location Prediction of a Moving Patient to Prevent the Accident -- An MDE Parameterized Transformation for Adaptive User Interfaces -- Agent Based MPEG Query Format Middleware for St